2002
DOI: 10.1021/ar010049p
|View full text |Cite
|
Sign up to set email alerts
|

How To Get the Most Out of Two Phosphorus Chemistries. Studies on H-Phosphonates

Abstract: The biological importance and practical significance of phosphate esters and their analogues have been the major driving forces for research in various areas of synthetic organic phosphorus chemistry. In this Account, the authors' studies on the development of a comprehensive H-phosphonate methodology and the underlying chemistry for the preparation of biologically important phosphate esters and their analogues are briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
84
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(90 citation statements)
references
References 74 publications
0
84
0
Order By: Relevance
“…It is important to know that the share of each tautomer is different when the connected groups to the phosphorus atom are changed. In the reported studies, it has been shown that electron-donating alkyl and aryl groups stabilize the phosphine oxide tautomer while electron-withdrawing substituents, such as trifluoromethyl, stabilize the phosphinous acid structure [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to know that the share of each tautomer is different when the connected groups to the phosphorus atom are changed. In the reported studies, it has been shown that electron-donating alkyl and aryl groups stabilize the phosphine oxide tautomer while electron-withdrawing substituents, such as trifluoromethyl, stabilize the phosphinous acid structure [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…1 Due to known separation problems, many recent efforts in the Mitsunobu reaction research have been directed toward modifying triphenylphosphine and azodicarboxylate reagents 3,4 to facilitate purification procedures, or to develop special, usually chromatographyfree, separation strategies. 4,5 As part of our program in developing synthetic methods for biologically important phosphates and their analogues based on H-phosphonate chemistry, 6,7 we became interested in the Mitsunobu reaction for two reasons. Firstly, it permits a condensation to be carried out under mild, virtually neutral conditions, and secondly, it involves activation of a hydroxyl function of an alcohol, rather than conversion of a pronucleophile into a reactive species.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, this methodology can be readily extended to other molecules which have a free hydroxyl group. 15,28 …”
mentioning
confidence: 99%